Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Optima Smartindo Industry - Nurul Aji Saubirin; Warsono Warsono (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2026)
Human resources play a strategic role in supporting the achievement of company objectives, particularly in improving employee performance. Optimal performance is influenced by various internal factors, including work motivation and work discipline. This study aims to examine the effect of motivation and work discipline on employee performance, both partially and simultaneously, at PT. Optima Smartindo Industry. The research employed a quantitative approach using a survey method involving warehouse employees and production operators as respondents, with a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression, supported by validity tests, reliability tests, classical assumption tests, t-tests, F-tests, and the coefficient of determination. The results indicate that motivation and work discipline each have a positive and significant effect on employee performance, and simultaneously both variables significantly influence employee performance. These findings suggest that improving employee performance can be achieved through strengthening work motivation and consistently implementing work discipline.